2015
DOI: 10.1371/journal.pone.0132694
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bacterial Burden and Cytokine Gene Expression in Golden Hamsters in Early Phase of Infection with Two Different Strains of Leptospira interrogans

Abstract: Leptospirosis, a zoonotic infection with worldwide prevalence, is caused by pathogenic spirochaetes of Leptospira spp., and exhibits an extremely broad clinical spectrum in human patients. Although previous studies indicated that specific serovars or genotypes of Leptospira spp. were associated with severe leptospirosis or its outbreak, the mechanism underlying the difference in virulence of the various Leptospira serotypes or genotypes remains unclear. The present study addresses this question by measuring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…MIP-1α/CCL3 was overexpressed in hamster while significantly down-regulated in mouse kidneys. Previous study also showed an overexpression of MIP-1α/CCL3 in the kidneys of hamster 4 days after infection with a virulent Leptospira strain [ 64 ]. MIP1-α/CCL3 belongs to the CC chemokine family that act on recruitment of several leukocytes [ 65 ], and up-regulation of this chemokine was suggested to be responsible for the recruitment of leukocytes in glomeruli in patients with glomerulonephritis [ 66 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…MIP-1α/CCL3 was overexpressed in hamster while significantly down-regulated in mouse kidneys. Previous study also showed an overexpression of MIP-1α/CCL3 in the kidneys of hamster 4 days after infection with a virulent Leptospira strain [ 64 ]. MIP1-α/CCL3 belongs to the CC chemokine family that act on recruitment of several leukocytes [ 65 ], and up-regulation of this chemokine was suggested to be responsible for the recruitment of leukocytes in glomeruli in patients with glomerulonephritis [ 66 ].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, its up-regulation is related to interstitial fibrosis and nephritis in rats [ 70 ] and to human glomerulonephritis [ 71 ]. IP-10/CXCL-10 transcript level was previously quantified in kidneys from hamsters infected with virulent leptospires and showed an increase of the gene expression during the acute phase of infection [ 64 , 72 ]. Herein, IP-10/CXCL10 was also overexpressed in the kidneys of both animal models during the carrier state, with a higher up-regulation in hamsters compared to mice.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from kidney tissues by using an RNeasy minikit and transcribed by using a high-capacity cDNA reverse transcription kit. cDNA was subjected to PCR using SYBR green and primers for CCL3 (MIP-1␣), CxCL10 (IP-10), TNF-␣, IFN-␥, IL-6, IL-10, and ColA1, as described previously (34,35). PCR data are reported as relative increases in mRNA transcript levels using ␤-actin as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from kidney tissues using a RNeasy mini kit and transcribed using a high-capacity cDNA reverse transcription kit. cDNA was subjected to real-time PCR using SYBR Green and primers as previously described (27), (28). PCR data are reported as the relative increase in mRNA transcript levels of MIP1-α (CCL3), IP-10 (CXCL10), TNF-α, IFN-γ, IL-4, IL-6, IL-10, iNOS and ColA1 of male and female hamsters infected with L. interrogans using β-actin as an internal control.…”
Section: Methodsmentioning
confidence: 99%